Lifelong training program on QGIS tools for earth observation sciences in south-east Europe - Bashkim IDRIZI; Lyubka PASHOVA; Pal NIKOLLI (European Journal of Geography)
Earth Observation (EO) data are an indispensable source of useful geospatial information, which can be efficiently combined with other data within the latest released open-source QGIS software. This paper aims: i) to present a general overview of the QGIS EO plugins; ii) to promote the Lifelong Learning (LLL) courses for open-source QGIS software tools provided by the Geo-SEE Institute from Skopje; iii) to appreciate the advantages of open-source QGIS for developing and improving EO applications. The training objectives are to enhance the research, development tools and technologies of QGIS and stimulate the obtaining and disseminating knowledge to utilize the open-source GIS software. Furthermore, there is a growing need to increase the number of well-educated professionals on issues related to the EO sciences in South-East Europe (SEE), who are better prepared for the labor market in today's digital revolution by using QGIS tools and plugins combined with other related GIS software platforms provided by the OSGeo family.